A citizen science approach to provide improved seeds to 1.3 million Ethiopian farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
New seeds need to be tested, but often the space and funds for testing are limited. CCAFS and Bioversity International supported the Integrated Seed Sector Development Ethiopia (ISSD Ethiopia) to implement a crowd-sourced, citizen science approach that provides a cost-effective solution.